Mutations in KRAS: are they a valid biomarker for pancreatic ductal adenocarcinomas diagnosis? - Narayanan, Vilvapathy; Konstantinov, Sergey R.; Peppelenbosch, Maikel P. (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Of all cancers, pancreatic cancer is associated with the most detrimental clinical outcome. Even when treated according to most recent guidelines, more as ninety percent of patients will not survive the cancer beyond one to five years after diagnosis (1). Compounding the clinical problem posed by pancreatic cancer is its sheer size: no less as 337,872 cases were reported in 2012 and the number of cases is still increasing every year (2).